Geographic variation in skull shape of the water rat Scapteromys tumidus (Cricetidae, Sigmodontinae): isolation-by-distance plus environmental and geographic barrier effects? - QUINTELA,FERNANDO M. (2016)
ABSTRACT The geographic variation in skull size and shape of the swamp rat Scapteromys tumidus was examined in samples from eight geographic clusters in almost of its distribution in southern Brazil and Uruguay. For analysis we used two-dimensional geometric morphometric methods for dorsal, ventral and lateral views of the skull. The geometric descriptors showed no significant differences in skull size between geographic clusters, while differences in shape were highly significant. We found a significant and moderate correlation between geographic and morphological distances, corroborating the isolation-by-distance model. Samples from the Rio Grande do Sul central coastal plain were the most differentiated, segregating completely from all other samples in canonical variate analysis for the dorsal view. The most visible variable regions in skull were the zygomatic arch (mainly the squamosal root of zygomatic) and the lateral braincase borders. Once correlation between geographic and morphological distances were not strong, it is possible that other factors (environmental heterogeneity and/or geographic barriers) may are acting in S. tumidus skull differentiation.